Success Factors and Barries in the Implementation of Load-Bearing Masonry System: The Case Study of Construction Firms in Malaysia - Nor Azlinda Ramli; Mohd Nasrun Mohd Nawi; Che Sobry Abdullah; Nazim Baluch; Ahmad Yusni Bahaudin (International Journal of Supply Chain Management, 2016)
This paper aims to investigate the adoption of Load Bearing Masonry LBM system among Malaysian housing developer companies as an important aspect in decision making process. A model based on the Information Diffusion Theory (IDT) was developed and tested using the Partial Least Square (PLS) approach. The research model has proposed that the perception of the organization such as the relative advantage towards LBM system adoption has a positive influence by the organizational readiness and external supports. A questionnaire was prepared to randomly collect the data. The questionnaires were distributed to the companies in Peninsular Malaysia only. The findings indicate that the relative advantage from Rogers innovation characteristics appears as the factor for the adoption of LBM system as well organizational readiness and external support. This paper to encourage policy makers to consider these factors in future actions plans to enhance the adoption of LBM systems in the construction industry especially in housing development.